Mechanism research and discussion of the quality of precision machining of a fifth-order variable-diameter pipe using abrasive flow - Li, Junye (Strojniški vestnik, 2020)
The solid-liquid two-phase abrasive flow precision machining technology is widely used in aerospace, precision machinery, the automotive industry and other fields, and is an advanced manufacturing technology that effectively improves the inner surface quality of workpieces. In this paper, the fifth-order variable-diameter pipe parts are researched. By discussing the collision between the abrasive particles and the wall surface, it is revealed that the material removal of the workpiece is caused by plastic deformation, and the mechanism of precision machining of the abrasive flow is clarified. Through numerical analysis and experimental research, it is found that the incident angle can affect the precision machining quality of the abrasive flow. When the inlet velocity of the abrasive flow is 45 m/s and the incident angle is 15°, the fifthorder variable-diameter pipe can obtain the best surface quality. Abrasive flow machining improves the surface quality of small holes better than that of large holes. To obtain uniform surface quality, it is necessary to use two-way machining to perform abrasive flow machining. The surface texture of the fifth-order variable-diameter pipe workpiece after precision machining by abrasive flow becomes clear and smooth, and the surface quality is significantly improved. The research results can provide theoretical guidance and technical support for the popularization and application of solid-liquid two-phase abrasive flow precision machining technology, with significant academic value and application value.
Keywords: abrasive flow precision machining; cev variabilnega premera; kakovost površine; numerical analysis; numerična analiza; odnašanje materiala; poliranje z abrazivnim curkom; quality control; teorija sklopitve CFD-DEM; variable-diameter pipe